Produção de (Signos) Interpretantes Mediada pela Tecnologia em Atividades de Modelagem Matemática - Chulek, Carina (2020)
In this investigation, we assume Mathematical Modeling as a pedagogical alternative that allows students to approach problem situations of their reality or interest. In this context, Mathematical Modeling is an alternative that provides students with conditions to learn mathematics, as well as acquire knowledge from other areas and use tools from their environment, such as software. It is in the development of mathematical modeling activities that the search for solutions to problems occurs, this search that may have been enunciated by the students, by the teacher, or by an agreement between both, we aim to analyze the signs produced by the students during activities of mathematical modeling developed from images and with recurrence to GeoGebra, and which had their problems proposed by them. To discuss these interpretative (signs), we present two activities of mathematical modeling developed by students of a 1st year of High School, from a private school, in the municipality of Pitanga - Paraná. The question that guides our investigation is: which signs are produced and in the activities of mathematical modeling are developed from the images, with the recurrence. As a result we consider that the interpretantes produced by the students during the course of the activities of the mathematical modeling undertaken by it, reveal the (in) knowledge of the mathematical and non-mathematical. In addition to this, these interpretants elicit students ' reflections on the insights which have emerged, and why they are built or deployed and lead to the generation of new signs. Also, the actions and directions taken by the students during the course of each and every one of the activities of the mathematical modeling, are associated with the signs that they have been produced, enable them overcome the difficulties related to the making of Mathematical Modeling and to build up knowledge on the GeoGebra, in the Mathematics, and the situation at hand.